2015
DOI: 10.1002/jctb.4729
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different modes of operation for the production ofSpirulinasp.

Abstract: BACKGROUND: Semi-continuous microalgae cultivations are large-scale production alternatives that maintain high microorganism growth rates. Studies show that semi-continuous cultivation can be conducted in two ways. In one, a blend concentration is set for the linear phase. The other uses a time interval dilution. This present work aimed to determine which mode of semi-continuous cultivation of Spirulina sp. LEB 18 presented the best kinetic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Semi-continuous cultures with shorter growth cycles tend to produce higher concentrations of biomass and productivity, since the higher the renewal rate, the lower the biomass concentration and the greater the availability of light (MOREIRA et al, 2016). This phenomenon was also observed in our study because when the renewal rate was high, the cell concentrations obtained were lower.…”
Section: Resultssupporting
confidence: 82%
“…Semi-continuous cultures with shorter growth cycles tend to produce higher concentrations of biomass and productivity, since the higher the renewal rate, the lower the biomass concentration and the greater the availability of light (MOREIRA et al, 2016). This phenomenon was also observed in our study because when the renewal rate was high, the cell concentrations obtained were lower.…”
Section: Resultssupporting
confidence: 82%
“…Our results are similar compared to a continuous cultivation system that used 90% of POME and resulted in 65 mg L −1 day −1 biomass productivity (Suharyanto et al 2014). By employing the semi-continuous system, inhibitory factors such as selfshading and excess secondary products secreted by the cells could be avoided, thereby resulting in higher biomass productivity (Radmann et al 2007;Moreira et al 2016). By using seawater for cultivation, a dual benefit was achieved: the salinity could be increased at the first stage and the demand of freshwater or drinking water could be lowered, overall reducing the cost of cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional and environmental factors such as salinity, irradiance, nitrogen availability, and cultivation mode (batch, semi-continuous, or continuous) regulate pigment productivity (Bezerra et al 2011;Liu et al 2016;Ho et al 2018). The biomass (expressed as dry weight) productivity of A. platensis could be enhanced by employing semi-continuous batch cultivation to prevent nutrient limitation and self-shading (Radmann et al 2007;Moreira et al 2016). With respect to wastewater utilization, Chaiklahan et al (2010) reported that cultivation of A. platensis on pig wastewater supplemented with bicarbonate and urea by employing a semi-continuous cultivation mode could press the cost of commercial medium up to 4.4 times compared to modified Zarrouk medium.…”
Section: Introductionmentioning
confidence: 99%